2019
DOI: 10.1002/ags3.12236
|View full text |Cite
|
Sign up to set email alerts
|

Current status of postoperative infections after digestive surgery in Japan: The Japan Postoperative Infectious Complications Survey in 2015

Abstract: Aim To survey postoperative infections (PI) after digestive surgery. Methods This survey, conducted by the Japan Society of Surgical Infection, included patients undergoing digestive surgery at 28 centers between September 2015 and March 2016. Data collected included patient background characteristics, type of surgery, contamination status, and type of PI, including surgical site infection (SSI), remote infection (RI), and antimicrobial‐resistant (AMR) bacterial infections and colonization. Results Postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…An observational study in Japan reported a POI incidence of 10.7% in 6582 patients who underwent GI surgery (6.8% for endoscopic surgery and 18.7% for open surgery) in 2015. In addition, the incidence rates of SSI in the biliary tract, pancreas, and esophagus were approximately 32.4%, 31.2%, and 20.1%, respectively, which were remarkably higher than those in other surgical sites [1].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…An observational study in Japan reported a POI incidence of 10.7% in 6582 patients who underwent GI surgery (6.8% for endoscopic surgery and 18.7% for open surgery) in 2015. In addition, the incidence rates of SSI in the biliary tract, pancreas, and esophagus were approximately 32.4%, 31.2%, and 20.1%, respectively, which were remarkably higher than those in other surgical sites [1].…”
Section: Introductionmentioning
confidence: 79%
“…Bacterial infection was confirmed by bacterial isolation. Bacterial colonization was defined as the presence of low-volume bacteria [1]. Data were collected to determine the infection and colonization status of the following antimicrobial-resistant bacteria: Clostridioides difficile, methicillin-resistant Staphylococcus aureus, and extended-spectrum beta-lactamase-producing Enterobacteriaceae [9][10][11].…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this need, the Japan Society of Surgical Infection organized the Japan Postoperative Infectious Complications Survey in 2015 to perform a multicenter joint study of the incidence of postoperative infection in digestive surgery. 7 The present report is a subanalysis of these data, for colorectal surgery.…”
Section: Introductionmentioning
confidence: 97%